Private Costs of Patients Hospitalized with Community-Acquired Pneumonia - Philip Jacobs; Thomas J Marrie; Peter Calder (Canadian Respiratory Journal)
BACKGROUND: Community-acquired pneumonia (CAP) is a condition which frequently requires hospitalization and consequently, can result in high costs. Little is known of the additional personal resources that are used by patients hospitalized for CAP.